Bleaching during orthodontic treatment and its effect on bracket bond strength - Sardarian, Ahmadreza (Dent Res J (Isfahan), 2019)
BACKGROUND: This study investigated the effect of two different methods of bleaching during orthodontic treatment on bracket bond strength. MATERIALS AND METHODS: A total of 45 extracted premolar teeth were selected in this experimental study and divided into three groups (office bleaching with 35% hydrogen peroxide, home bleaching with 22% carbamide peroxide, and control). The color of the teeth was assessed initially before the application of bleaching agents and Thermocycling. Orthodontic brackets were subsequently bonded on the treated surfaces. Bleaching procedures were then performed. A final color measurement was performed at two points on the buccal surface both underneath and adjacent to the bracket base. The initial and final color measurements and the bond strengths were compared between the groups using the analysis of variance. P < 0.05 was considered as statistically significant. RESULTS: Bracket bond strength was significantly reduced in both bleaching groups compared with the control group (P < 0.01). The color difference before and after the bleaching procedures was significant in the office bleaching group (P < 0.01), while the control group did not demonstrate a statistical difference between initial and final color assessments (P > 0.05). CONCLUSION: Bleaching procedures performed during orthodontic treatment reduce bond strength. Enamel beneath the bracket base experiences a whitening effect though to a lesser degree compared with an uncovered surface.